Genetic Variation in Shiga Toxin-producing Escherichia coli Recovered from Patients in Michigan and Connecticut - Selheimer, Heather (Open Forum Infect Dis, 2017)
BACKGROUND: Shiga toxin-producing Escherichia coli (STEC) is a gram-negative foodborne pathogen that causes approximately 265,000 illnesses in the US annually. STEC O157 and six non-O157 STEC serotypes are most commonly associated with illness, though variation exists in the ability of different STEC types to cause disease. Consequently, we sought to examine genetic variation in virulence genes and clustered regularly interspaced repeat (CRISPR) loci among clinical strains of diverse lineages from different geographic locations. METHODS: Isolates were collected from a sentinel surveillance in 2000–2006 by the Michigan Department of Health and Human Services (n = 44) and Connecticut Department of Public Health (n = 115). Whole genome sequencing was performed and genes for O-antigen (serotype), multilocus sequence typing (MLST) and virulence factors were extracted. CRISPRFinder and Geneious were used for CRISPR loci. RESULTS: A phylogenetic tree based on MLST found no geographic clustering of the strains. Similarly, no difference was observed for stx1 (MI: 89.6%, CT: 83.5%), stx2 (MI: 6.9%, CT: 7.1%), stx1/stx2 (MI: 3.4%, CT: 9.4%), ehxA (MI: 80.0%, CT: 81.2%) and eae (MI: 86.7%, CT: 94.1%) frequencies across geographical locations. Although the CRISPR loci were similar within related STs, which was independent of serotype, some variation was detected between locations. CONCLUSION: These data highlight the circulation of common non-O157 STEC lineages capable of causing disease in different populations. Strains had similar virulence gene profiles, though the diversity of the CRISPR loci varied across strains. The latter could be impacted by varying selective pressures that could affect disease frequencies and symptom severity. Continued surveillance of non-O157 STEC is needed to elucidate the genetic characteristics that are most important for disease severity. DISCLOSURES: All authors: No reported disclosures.